Prediction of Unruptured Intracranial Aneurysm Evolution: The UCAN Project. Issue 1 (6th May 2020) - L'Allinec, Vincent; Chatel, Stéphanie; Karakachoff, Matilde; Bourcereau, Emmanuelle; Lamoureux, Zeineb; Gaignard, Alban; Autrusseau, Florent; Jouan, Solène; Vion, Anne-Clemence; Loirand, Gervaise; Desal, Hubert; Naggara, Olivier; et al.
Abstract: BACKGROUND: Management of small (<7 mm) unruptured intracranial aneurysms (UIA) remains controversial. Retrospective studies have suggested that post gadolinium arterial wall enhancement (AWE) of UIA on magnetic resonance imaging (MRI) may reflect aneurysm wall instability, and hence may highlight a higher risk of UIA growth. This trial aims at exploring wall imaging findings of UIAs with consecutive follow-up to substantiate these assumptions. OBJECTIVE: To develop diagnostic and predictive tools for the risk of IA evolution. Our aim is to demonstrate in clinical practice the predictive value of AWE for UIA growth. The growth will be determined by any modification of the UIA measurement. UIA growth and the UIA wall enhancement will be assessed in consensus by 2 expert neuroradiologists. METHODS: The French prospective UCAN project is a noninterventional international wide and multicentric cohort. UIA of bifurcation between 3 and 7 mm for whom a clinical and imaging follow-up without occlusion treatment was scheduled by local multidisciplinary staff will be included. Extensive clinical, biological, and imaging data will be recorded during a 3-yr follow-up. EXPECTED OUTCOMES: Discovering to improve the efficiency of UIA follow-up by identifying additional clinical, imaging, biological, and anatomic risk factors of UIA growth. DISCUSSION: A prospective nationwide recruitment allows for the inclusion of a large cohort of patients with UIA. It will combine clinical phenotyping and specific imaging with AWE screening. It will enable to exploit metadata and to explore some pathophysiological pathways by crossing clinical, genetic, biological, and imaging information.